Genetic epidemiology and heritability of AIS: A study of 415 Chinese female patients - Tang, Nelson L.S.; Yeung, Hiu-Yan; Hung, Vivian W.Y.; Di Liao, Chen; Lam, Tsz-Ping; Yeung, Hau-Man; Lee, Kwong-Man; Ng, Bobby Kin-Wah; Cheng, Jack Chun-Yiu (Journal of orthopaedic research, 2012)
Recent familial segregation studies supported a multifactorial genetic model for the etiology of adolescent idiopathic scoliosis (AIS). However, the extent of quantitative genetic effects, such as heritability, have not been fully evaluated. This genetic epidemiology study examined the sibling recurrent risk and heritability of AIS in first‐degree relatives of 415 Chinese female patients, which is up to now the largest cohort. They were first diagnosed by community screening program and compared to 203 age‐matched normal controls. Out of the total 531 sibs of AIS cases, 94 sibs had scoliosis (sibling recurrence risk = 17.7%). The prevalence of AIS among male and female sibs of an index case were 11.5% (95% CI = 7.5–15.5) and 23.0% (95% CI = 18.1–27.9), respectively. Female sibs of an index case had an increased risk of 8.9‐fold (95% CI = 3.2–34.4) for developing AIS. These recurrent risks were significantly higher than the risk in the control group (p < 0.0001). Overall, heritability was estimated to be 87.5 ± 11.1%. The results confirmed the prevailing impression of strong genetic influence on the risk of AIS. Here we provided a large‐scale study for the genetic aggregation estimates in an Asian population for the first time. The finding also positioned AIS among other common disease or complex traits with a high heritability. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 30:1464–1469, 2012